Impact of postoperative acute kidney injury on predicting the upstaging of chronic kidney disease after robot‐assisted partial nephrectomy. Issue 1 (20th July 2020) - Teishima, Jun; Inoue, Shogo; Miyamoto, Shunsuke; Fukuoka, Kenichiro; Sekino, Yohei; Kitano, Hiroyuki; Hieda, Keisuke; Hayashi, Tetsutaro; Matsubara, Akio
Abstract: Introduction: The aim of our study was to assess the impact of acute kidney injury (AKI) on postoperative upstaging of chronic kidney disease (CKD) after robot‐assisted partial nephrectomy (RAPN). Methods: This study consisted of 110 patients who had undergone RAPN and were followed up for at least 6 months after surgery. Patients were classified as AKI or non‐AKI based on their serum creatinine level and estimated glomerular filtration rate within 7 days after surgery. Patient characteristics, outcome of RAPN and estimated glomerular filtration rate, and CKD upstage 6 months after surgery were compared between the AKI and non‐AKI groups. Results: A total of 26 patients (23.6%) experienced AKI after surgery. RENAL (radius, exophytic/endophitic properties, nearness of the tumor to the collecting system or sinus, anterior/posterior, location relative to the polar lines) nephrometry scores were ≥7 for 22 (84.6%) in the AKI group and 39 (46.4%) in the non‐AKI group ( P = .0006). A significantly smaller proportion of patients in the AKI group than in the non‐AKI group recovered 90% of baseline function (38.5% vs 81.0%, P < .0001). CKD upstaging occurred in a total of 27 patients 24.5%) and in a significantly larger proportion of patients in the AKI group than in the non‐AKI group (42.3% vs 19.0%, P = .0160). There was no significant difference in characteristics and perioperative outcomes between the patients with and without CKD, except for in those experiencing AKI. Conclusion: After RAPN, AKI can be associated with CKD upstaging.